2022
DOI: 10.1002/hbm.26057
|View full text |Cite
|
Sign up to set email alerts
|

Neural efficiency and proficiency adaptation of effective connectivity corresponding to early and advanced skill levels in athletes of racket sports

Abstract: This study explored how the neural efficiency and proficiency worked in athletes with different skill levels from the perspective of effective connectivity brain network in resting state. The deconvolved conditioned Granger causality (GC) analysis was applied to functional magnetic resonance imaging (fMRI) data of 35 elite athletes (EAs) and 42 student‐athletes (SAs) of racket sports as well as 39 normal controls (NCs), to obtain the voxel‐wised hemodynamic response function (HRF) parameters representing the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…Previous resting-state comparisons between table tennis athletes and nonathletes have revealed that athletes exhibit improved structural integrity with regard to white matter fiber bundles [56] and superior brain functional connections [57]. These training-induced neural adaptations, which are indicative of efficient connectivity, have been identified in athletes who participate in racket sports, including tennis and table tennis [58]. Furthermore, a correlation between lower activation in the frontoparietal attention network and higher world rankings among table tennis players has been documented, thus reinforcing the claim that specific neural efficiencies contribute significantly to elite sports performance [59].…”
Section: Discussionmentioning
confidence: 99%
“…Previous resting-state comparisons between table tennis athletes and nonathletes have revealed that athletes exhibit improved structural integrity with regard to white matter fiber bundles [56] and superior brain functional connections [57]. These training-induced neural adaptations, which are indicative of efficient connectivity, have been identified in athletes who participate in racket sports, including tennis and table tennis [58]. Furthermore, a correlation between lower activation in the frontoparietal attention network and higher world rankings among table tennis players has been documented, thus reinforcing the claim that specific neural efficiencies contribute significantly to elite sports performance [59].…”
Section: Discussionmentioning
confidence: 99%
“…This effect of familiarity also extends into specific categories of action experience. For example, expert athletes such as professional dancers or those engaged in ball-related sports exhibit greater accuracy in predicting, perceiving, and comprehending human movements within their respective domains of expertise (Poulton, 1957;Cross, Hamilton, & Grafton, 2006;Aglioti et al, 2008;Makris & Urgesi, 2015;Romeas & Faubert, 2015;Chang, Chen & Yen, 2018;Apšvalka, Cross & Ramsey, 2018;Wang, Ji & Zhou, 2019;Chen et al, 2020;Chen et al, 2022;Gao et al, 2022;For a review, see Smith, 2015). Moreover, emerging evidence suggests that deaf people demonstrate faster and less effortful perception of point-light displays (PLDs) than hearing non-signers, suggesting that being deaf may lead to a similar expertise effect with biological motion perception.…”
Section: Biological Motion Perceptionmentioning
confidence: 99%
“…Previous studies solely relied on functional connectivity and effective connectivity to analyze the connection relationships between local brain regions. However, delving into the topological properties of the whole brain network has provided a deeper understanding of this connectivity [ 33 , 34 , 35 ]. The examination of whole-brain topological properties unveils the overall structure and characteristics of the brain network, along with the connection patterns and topological features among diverse brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, with advancements in human brain connectomics, it has become evident that the human brain does not operate in isolation; rather, it exhibits close connections between different regions and operates in coordination through specific connection patterns with efficient network transmission characteristics [32]. Previous investigations into brain networks among TTAs have primarily emphasized functional connectivity and efficiency connectivity [33,34]. For instance, Li et al (2023) [33] observed reduced static functional connectivity in the right middle temporal gyrus and left inferior parietal gyrus among individuals with TTAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation